A multielement alloying strategy to improve elastocaloric and mechanical properties in Ni–Mn-based alloys via copper and boron. (August 2020) - Huang, Xiao-Ming; Zhao, Ying; Yan, Hai-Le; Jia, Nan; Tang, Shuai; Bai, Jing; Yang, Bo; Li, Zongbin; Zhang, Yudong; Esling, Claude; Zhao, Xiang; Zuo, Liang
Abstract: Ni–Mn-based shape memory alloy is a promising candidate as the solid-state elastocaloric refrigerant in the micro- or nano-refrigeration fields owing to the required small driving force. In this letter, we report a multielement alloying strategy, i.e., the co-substitution of non-magnetic element and boron for Mn, to improve the elastocaloric refrigeration efficiency and mechanical properties simultaneously. Under Cu and B co-substitution, a large adiabatic temperature change of –12.8 K and a giant specific adiabatic temperature change of 41.0 K/GPa were obtained in the directionally solidified Ni50 (Mn31.7 Cu2.5 B0.3 )In15.5 alloy. The proposed alloying manner is also favorable to enhance fracture resistance and cyclability. Graphical abstract: Image, graphical abstract